The Impact of Fringe Benefits on Employee Performance: A Case Study of Uganda Christian University Mukono District - Esther Temple Kugonzakwe (Uganda Christian University, 2024)
The study aimed to investigate the impact of fringe benefits on employee performance. a case study of Uganda Christian university Mukono district. The study also had objectives such as to investigate whether employment security benefits influence employee performance in the study context, to analyse whether health protection benefits influence employee performance in the study context and to examine whether retirement benefits influence the performance of employees in the study context. The study were conducted over a period of one month, and it was limited to the university located at Plot 67-173, Bishop Tucker Road. The study's significance lies in its ability to offer valuable insights to the government in terms of formulating policies related to employee compensation packages. The study may also serve as a basis for recommending tax incentives or financial subsidies for organizations that provide more comprehensive and effective fringe benefits to employees. Additionally, the study's findings may assist organizations in designing and implementing effective compensation packages that lead to a more engaged and satisfied workforce. Furthermore, the study's results can be used as a reference point for further research on the topic. The study used a descriptive research design, combining quantitative and qualitative methods. The sample size for this study is 36 respondents, both staff and non-staff of Uganda Christian University, determined using the Yamane's formula. Information to aid this study shall be obtained from both primary and secondary sources, while methods of data collection shall include self-administered questionnaires, personal interviews, and reviews of documents. The questions in the questionnaire shall be closed-ended. It was noted that data showed that employment security benefits, such as full training policy and good overtime planning, were crucial in terms of employee performance. Also, health protection benefits, such as Occupational Health and Safety and Medical Insurance benefits, contributed to productivity gains through reduced stress levels and job satisfaction. Retirement benefits, which include pensions and savings plans, contributed positively to the productivity of employees because these provide financial security and help maintain workforce stability. The monetary benefits, such as bonuses and discounts, were significant in raising morale and productivity. The survey results supported recent scholarly literature on stressing a customized benefit package as one of the contributing variables toward a productive workplace.